Seleção e caracterização fenotípica de variedades de tangerinas e híbridos - Cellere, Luiz Otavio Ribeiro (Universidade Federal de São Carlos, 2025)
Brazilian citriculture is increasingly seeking new varieties with desirable characteristics. High productivity, resistance to pathogens and stress, and good fruit quality indices all of these aspects, when found in promising varieties, contribute to the current scenario of citriculture. This study aimed to select, among dozens of materials under field evaluation, those varieties with the greatest commercial potential and to characterize them phenotypically. For this purpose, plant height and canopy diameter were measured, and canopy volume was calculated. In addition, evaluations were conducted regarding resistance to Alternaria brown spot. For productivity analysis, counts of green fruits were performed, along with the weighing of mature fruits and calculation of their averages to estimate yield. Furthermore, during the maturation period, 10 fruits were periodically collected for physical-chemical quality analysis (three replications), and the number of seeds per fruit was recorded. After the evaluations, 34 promising varieties were selected, including 16 common mandarins, 11 "Ponkans", six Willowleaf mandarin and one Clementine.
Selection and phenotypic characterization of tangerine varieties and hybrids
Keywords: Citros; Alternária; Citrus reticulata; Alternária; Produtividade; Citrus; Willowleaf mandarin; Alternaria; Productivity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA